Industry Application of Green Manufacturing: A Critical Review - Saxena, Ankur; Srivastava, Ankita (Journal of Sustainability and Environmental Management, 2022)
Green manufacturing is the minimization of hazardous matter in the process of designing, production and technology which may affect the domain of the earth and lead towards global warming. It generally refers to broad area including air, water and land pollution, energy usage and efficiency, waste generation and recycling. It is well known fact that production of greenhouse gases (N2O, CO2 and CH4) which are measured to calculate the carbon footprint majorly affect the global warming. Hence to save the environment, it is most significant to decrease the carbon footprint of a sector. Researchers have agreed that one of the main reasons for global warming is Industrialization, and green manufacturing can be considered an effective tool to control and minimize the GHG emission from Industries so this paper will review the application of green manufacturing across the industries including transportation, electricity generation, cement industry, textile and apparel industry etc. DOI: https://doi.org/10.5281/zenodo.6207141